Where is Igglepiggle's blanket? - Davenport, Andrew (London : BBC Children's Books, 2008)
"One day, Igglepiggle's lost his blanket. Don't worry Igglepiggle, we'll find your blanket."--Cover.
Keywords: Children's stories